Territorial and Temporary Spread of COVID-19 in the World at the Beginning of the 2020 Pandemic - I. S. Karpova; K. A. Stolyarov; N. M. Popovtseva; T. P. Stolyarova (Эпидемиология и вакцинопрофилактика)
Relevance. COVID-19 remains a serious problem for all countries of the world, affecting all areas of public life. The brunt of the problem falls on health care. The new coronavirus infection has raised many questions, in particular regarding its epidemiologyAim. Determine the sequence of the global spread of COVID-19 at the beginning of the 2020 pandemic and the possible influence of seasonality on its distribution.Materials and methods. Data on the countries of the Northern and Southern hemispheres of the sites «Our World in Data» from the section «Coronavirus (COVID-19) Cases». Стопкоронавирус.рф, Johns Hopkins University were used. The analysis of the spread of COVID-19 in the world was carried out based on data on the incidence and deaths from COVID-19 by climatogeographic zones.Results and discussion. The sequence of the spatio-temporal spread of COVID-19 across countries and continents at the beginning of the pandemic in 2020 has been determined. The similarity of the global spread of COVID-19 and "seasonal" influenza A(H3N2) epidemics indicates the spread of these infections along the primary migration routes of the population. The global spread of the COVID-19 pandemic virus, as well as influenza A(H1N1), was sufficient for 1–1.5 months. The COVID-19 pandemic began in the Northern Hemisphere in the spring and summer, but atypical seasonality was often observed at the beginning of influenza pandemics. On the other hand, data on the influence of seasonality on the spread of COVID-19 were obtained: the highest incidence in the Northern Hemisphere countries was in the winter, and in the Southern Hemisphere countries, with reverse seasonality, a high incidence was observed already in the summer months. Therefore, it will be possible to make a final conclusion about the seasonality of this infection in the following years.